MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA ISLAM UNTUK MASYARAKAT MULTIKULTUR - Ahmad Faozan (Hikmah: Journal of Islamic Studies, 2020)
Abstract This article proposes the whole-school approach model, an approach to put multicultural education as strategy to involve all the stakeholders of schools in one system. Islamic education is a sub system of multicultural national education system. Religious moderation in Islamic education is a hidden curriculum, to present Islam as moderate religion, not to serve religious subject as violence and extremism. The strategy or religious moderation can be seen from some aspects, such as teacher, textbook and extra-curricular activities. Abstrak Artikel ini menawarkan model whole-school approach, pendekatan yang memandang pendidikan multikultural sebagai sebuah strategi pendidikan yang melibatkan semua elemen sekolah sebagai sebuah sistem. Pendidikan Agama Islam merupakan sub sistem dari sistem pendidikan nasional yang multikultural. Moderasi beragama dalam pendidikan agama Islam dijadikan sebagai hiidden curriculum berarti cara mengajarkan pendidikan agama Islam yang moderat, bukan pendidikan agama yang mengajarkan kekerasan dan keekstreman. Strategi moderasi beragama dalam pendidikan agama Islam untuk masyarakat Indonesia multikultural dapat dilihat dari beberapa aspek antara lain guru, buku ajar dan kegiatan ekstrakurikuler.